Lack of sleep and unethical conduct - Barnes, Christopher M.; Schaubroeck, John; Huth, Megan; Ghumman, Sonia (Organizational behavior and human decision processes, 2011)
We draw from the Ego Depletion model and research on sleep physiology to predict a relationship between lack of sleep and individuals’ unethical behavior. Laboratory studies showed that sleep quantity is positively related to self-control resources and negative associated with unethical behavior. In a cross-sectional field study examining unethical behavior in a variety of work settings, low levels of sleep, and low perceived quality of sleep, were both positively related to unethical behavior as rated by the supervisor, and cognitive fatigue mediated the influence of sleep quantity. In an experience sampling field study, we found similar effects within-individuals. We discuss the role of lost sleep in better understanding unethical behavior in organizations.